STUDY OF CHANGES IN CURRANT DURING FAST FREEZING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Frozen berries have a number of undeniable advantages: they do not require additional preparation costs, are almost ready to eat, and most importantly, thanks to modern technologies, they retain almost twice as much nutrients as with other canning methods. Increasingly, there are risks associated with internal and external factors, as well as problems with excess yields that threaten not to sell the product fresh. short shelf life immediately after harvest, which increases the critical dependence on market prices. One of the progressive technological methods of processing fruit and berry products is quick freezing. The use of such freezing gives, first of all, a low degree of product damage, minimally reduces the biological value and taste characteristics, and the use of freezing does not significantly affect the quality of the thawed product.The main task of an industrial or commercial line for shock freezing of berries is to ensure almost instantaneous preservation of the product, which will retain all its nutritional value and taste. This is usually achieved by rapidly chilling the berries to -18 °C. By far the best option for extending the shelf life of freshly cooked food is to freeze it quickly. There are various options, but the best known is the freezing technology. For instant freezing without crystallization, it is necessary to provide a temperature of -5 ...- 18 °C. Experimental data were obtained during research. The temperature regime of storage of currants with the preservation of quality indicators using a freezing device is also considered. When frozen quickly, the berries should be blown from all sides or literally float in a stream of frosty air of the appropriate temperature. The duration of this process depends on the type and size of the berries, as well as on the intensity of the cooling air flow. The current direction in the field of research of frozen berries is the preservation of consumer properties of berries after freezing